Experimental and CFD analyses of a highly-loaded gas turbine blade. (September 2017) - Bacci, Tommaso; Gamannossi, Andrea; Mazzei, Lorenzo; Picchi, Alessio; Winchler, Lorenzo; Carcasci, Carlo; Andreini, Antonio; Abba, Luca; Vagnoli, Stefano
Abstract: The estimation of metal temperature is paramount to ensure an adequate life span of gas turbine hot gas path components. An experimental campaign was carried to investigate pressure loading and metal temperature distribution of an industrial blade cooled by means of straight smooth channels. Changing mainstream and coolant mass flow rates it was thus possible to characterize the thermal response at different operating conditions. CFD simulations allowed to relate the metal temperature distribution to the processes of laminarization and transition of the boundary layer. Further sensitivity analyses aimed at estimating the impact of the uncertainty associated with certain boundary conditions highlighted that a reduction in mainstream turbulence at leading edge of 30% can reduce metal temperature up to 5%, whereas coolant turbulence plays a minor role. The same effect was pointed out when the actual surface roughness of the internal channels was accounted for. Particular attention should be paid to this parameter in the thermal design of additive manufactured components when surface finishing is not feasible.